Specialist mental health crisis centres in England: a step forward or a stumble in the dark? - Yasser Saeed Khan; Subodh Dave; Mohammed Al-Uzri; Javed Latoo; Ovais Wadoo (BJPsych Open)
The recent proposal by NHS England to establish specialist mental health crisis centres has prompted considerable discussion. This editorial examines the initiative, which aims to reduce accident and emergency pressure and provide tailored care. However, it raises significant questions about the potential to exacerbate systemic fragmentation. Concerns highlight inadequate funding, the risk of resegregation of mental health from physical care and increased stigma if not properly integrated. This article argues that true holistic care requires seamless integration, advocating strongly for co-located mental health and medical emergency departments, which have shown improved outcomes. Ultimately, the success of these centres depends on addressing wider NHS issues, robust evaluation and a comprehensive vision prioritising the entire mental health pathway, from prevention to long-term recovery, to genuinely transform patient lives.